El ordenamiento territorial en la contaminación acústica del área urbana de la ciudad de Riobamba - Cristina Gabriela, Cóndor Simbaña (2022)
ABSTRACT: This research, named "The territorial planning about the noise pollution in the urban area of Riobamba city" accounts for the need to face a current problem affecting this city and thus the local population, since the noise pollution levels is a threat to territorial sustainability and it usually goes unnoticed in the urban territory planning and ordering, therefore, this research, is intended to measure the noise pollution levels to determine such referential indicators for making decisions in the Riobamba city urban planning on this issues from means of spatial and geostatistics analysis. In this aim, a day-night noise pollution monitoring was carried out in 87 points randomly selected and homogeneously distributed in the urban area and in 12 downtown points in order to catch the population perception on this study matter, therefore the research technique used was the interview revealing 95%-confidence and, determining not only a population vulnerability to the high-levels noise pollution exposure which overcomes national and international thresholds but also the deficient urban territory planning and ordering to mitigate these high noise levels. From this study results, a noise management plan was made up as a tool for making decisions for noise levels reduction in Riobamba city.In the county of Tisaleo. All the conditions converge in several areas for urban growth for the cities of Tisaleo and Quinchicoto. Although no all of those zones meet the definition to be consider as a urban area. In the other side, there are cities that have been ignored such as Alobamba and Santa Lucia Arriba that are considered rural zones but meet all the characteristics studied to be considered a urban zone.